First retrospective study on pediatric nephrocalcinosis in Syria: clinical symptoms and causes - Hadeel Ghanem; Mostafa Hassan; Sarena Swideah; Hala Wannous (Frontiers in Pediatrics)
BackgroundNephrocalcinosis is the deposition of calcium oxalate and phosphate in the kidneys. It is often asymptomatic and diagnosed via ultrasound. Symptoms may include hematuria or sterile leukocyturia. Based on echogenicity, it is classified as medullary or cortical. Although it may pose a problem in developing countries, it has not been adequately studied in the Middle East.ObjectivesTo investigate the clinical manifestations and outcomes of nephrocalcinosis for the first time in Syria. And to establish a primary database for such studies in Syria and the Middle East region.MethodsThis retrospective study was conducted in a single pediatric nephrology department of a tertiary university hospital in Damascus, Syria. We collected the medical records of patients with a primary diagnosis of nephrocalcinosis between January 2014 and January 2018. All clinical, laboratory examination, treatment, and follow-up information were collected and analyzed.ResultsAmong 75 patients Forty-one (54%) were males and 34 (46%) were females, the median age at presentation was 18 months. The most presenting symptom was incidentally found in 39% of cases, then failure to thrive in 32% of cases, and recurrent urinary tract infections in 10.5% of cases. The most common leading cause of nephrocalcinosis was metabolic disorders in 68% followed by tubulopathy in 20%. The cause of nephrocalcinosis remained unknown in 8%, and renal malformations for 4% of the cases. During the study, five children developed end-stage renal disease (ESRD), and fifteen children died from different causes.ConclusionThis is the first Syrian study to review nephrocalcinosis cases. The most common leading cause of NC was metabolic disorders, most importantly, the patient with progressive nephrocalcinosis must be convinced that a high daily fluid intake is the most valuable therapeutic option.